PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID DAN KEARIFAN LOKAL TERHADAP MATERI TEKS NONFIKSI - Yuliana Novitasari; Kukuh Andri Aka; Rian Damariswara (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The background of the research in this article is derived from the author's desire to design an Android and local wisdom-based learning media that is easily accessible anytime and anywhere so that it is expected for students to attract their interest in learning about nonfiction text material. The purpose of the research was to determine the effect of using Android and local wisdom-based interactive multimedia on non-fiction text material. This research was conducted at SDN 1 Bendo Tulungagung and SDN Laboratory of Universitas Nusantara PGRI Kediri. The type of research was quantitative with experimental research methods. The conclusion could be seen from the statistical calculations of SDN 1 Bendo Tulungagung. It was obtained that the Pearson correlation value > rtable value was 0.580 > 0.433. Accordingly, the data from SDN 1 Bendo was valid. Meanwhile, from SDN Laboratory of Universitas Nusantara PGRI Kediri, it was obtained that the Pearson correlation value < rtable value was the Pearson correlation value < rtable value, it could be written as 0.489 < 0.576. Thus, it could be concluded that there was an effect of using Android and local wisdom-based interactive multimedia on non-fiction text material.